Vegetation history based on a multi-proxy analysis of sediment core Zamostye, Kursk region, Russia - Ekaterina Lukanina; Lyudmila S Shumilovskikh (PANGAEA, 2022)
The study site Zamostye (51.18481 °N, 35.27988 °E, 135 m a.s.l.) is situated in the south-west of the Mid-Russian Upland in the south of the East European Plain, in the center of the East-European forest-steppe ecotone. The knowledge of the history of the formation of the ecotone can help sustainability of the land management as well as show its response to climatic changes, however the area is considerably understudied. In order to close this gap, we conducted a study of the vegetation history based on a multi-proxy analysis of a sediment core obtained in the village Zamostye (Kursk region, Russia). The study site represents a wetland overgrown by Phragmites and surrounded by alder trees and grasslands with ruderal vegetation. The sediment core was obtained with a Russian corer from an overgrown oxbow lake near the river Sudzha in July 2013 and consists of two sister cores - “Zamostye I” (0-176 cm from surface) and “Zamostye II” (25-250 cm). The two cores were taken close to each other with overlapping segments and combined based on LOI results to obtain a composite core Zamostye. 11 radiocarbon ages were acquired to ensure a robust age-depth model. The core was studied for pollen, non-pollen palynomorphs, loss-on-ignition, macroremains and charcoal. Due to the lack of the archives like lakes and mires in the area, this record covering the last 14,800 years is unique for the region and provides a continuous vegetation history from the Late Glacial to the present. In total, 66 samples in 1 to 4-cm resolution were obtained for palynological, NPP and micro-charcoal analysis. Laboratory treatment followed the standard processing technique by Faegri and Iversen (1989) included 10 % HCl, 48 % HF left overnight and acetolysis for 3 minutes. The samples were then sieved through 200 μm metallic mesh and 6 μm nylon mesh using an ultrasound bath for less than 1 minute. Before the chemical treatment, one Lycopodium spores extquotesingle tablet (batch number 1031, 20848 ± 1546 spores per tablet) was added to each sample to calculate palynomorphs concentration and influx (Stockmarr, 1971). Macro-charcoal analysis was performed in 2-cm resolution. The samples were treated following Stevenson and Haberle (2005): 10 % KOH, 6 % H2O2 and sieved through 125 μm metallic mesh. The charcoal was identified under 100 exttimes magnification. Four morphological types were identified using Jensen et al. (2007). We analyzed 14 samples for macroremains to track the changes in local vegetation and sediment composition. The entire 1-cm thick section of the core was sieved through 250 μm and studied under 40 exttimes to 100 exttimes magnification. We used Cappers et al. (2006) and Göttingen University collection to identify the seeds of the plants.